Mechanisms of immunotherapy to wasp and bee venom - (:unkn) unknown (WILEY, 2011)
Hymenoptera venoms are important allergens that can elicit both local and systemic allergic reactions, including life-threatening anaphylaxis. Venom immunotherapy (VIT) remains the most effective treatment, reducing the risk of systemic reactions in individuals with Hymenoptera venom allergy. VIT can restore normal immunity against venom allergens and provide patients with a lifetime of tolerance to venoms. During VIT, peripheral tolerance is induced by the generation of allergen-specific regulatory T (Treg) cells, which suppress proliferative and cytokine responses against the venom allergens. Treg cells are characterized by IL-10 secretion that directly or indirectly influence effector cells of allergic inflammation, such as mast cells, basophils and eosinophils. Treg cells also have influence on B cells, suppressing IgE production and inducing the production of blocking type IgG4 antibodies against venom allergens. An accumulating body of evidence suggests that Treg cells may affect allergen sensitization and methods for enhancing this cell population may eventually improve the efficacy of VIT. In this article, immune mechanisms enrolled in bee and wasp VIT are reviewed.
Keywords: REGULATORY T-CELLS; SUBLINGUAL IMMUNOTHERAPY; IMMUNE-RESPONSES; DENDRITIC CELLS; HISTAMINE; CD4(+); EXPRESSION; ALLERGY; BETA; INTERLEUKIN-10